Examining agreement between coach prescribed and observed training loads with those that are reported by professional female soccer players - Wilmot, K.; Dello Iacono, A.; Macpherson, T. W. (The Journal of Strength and Conditioning Research, 2025)
There is no research exploring agreement of training load (TL) between players and coaches in female soccer, therefore, we examined agreement of perceived TL between professional female soccer players and their coaches. An observational research design was used with a professional women soccer team (3 coaches and 23 players), with data collected for an 8-week training period from a total of 20 training sessions. Internal TL was measured using differential ratings of perceived exertion (dRPE) on the original Borg CR-100 scale, with exertional scores taken for the overall ratings of perceived exertion, ratings of perceived exertion of breathlessness, ratings of perceived exertion on the legs, and technical ratings of perceived exertion. External TL was measured with PlayerData global positioning system units, worn during every training session, with total distance and high-intensity distance data selected for the study. Players and coaches were familiarized with dRPE and the CR-100 scale. Before training, coaches provided a training plan alongside prescribed dRPE and external load. After training, coach-observed dRPE and external load measures were collected alongside player-perceived dRPE. Two 1-sided tests assessed equivalence between coach (prescribed and observed) and player-perceived dRPE. Statistically significant equivalence was reported for agreement between coach (prescribed and observed) and player-perceived dRPE (p < 0.05). However, for both external TL measures, no statistical significance in agreement was reported between coaches and players. This study provides preliminary evidence of agreement between coach and player perceptions of TL in professional woman's soccer. This study provides a key finding in professional woman's soccer, potentially allowing greater precision in TL prescription and achieving desired training outcomes.